The Effectiveness of E-Learning in Iraqi Universities during the COVID-19 Pandemic: A Case Study of Selected Iraqi Universities and Institutes - Ahmed Abdul Adheem Al-Azzawi (Universal Teaching and Learning Journal, 2026)
Purpose: This study aims to investigate the effectiveness of e learning as implemented in Iraqi universities, colleges, and institutes during the academic year 2019/2020, with a particular focus on the challenges and outcomes arising from the COVID-19 pandemiccontext. The study evaluates how emergency remote instruction reshaped educational delivery in a country with pre-existing infrastructural deficiencies. Methodology: A descriptive-analytic research design was memployed. A structured online questionnaire was administered to  6,579 participants drawn from both public and private Iraqi higher education institutions. Data collection focused on students' and instructors' perceptions of platform usability, internet reliability, content quality, examination integrity, and institutional preparedness. Results: Findings reveal that Google Classroom was the dominant platform adopted by 87.2% of respondents. Internet connectivity emerged as the foremost barrier, cited by 61.8% of participants. Concerns about academic dishonesty were raised by 45.1% of respondents, while institutional support was rated as excellent by 27.8%. The majority of students experienced electronic examinations for the first time during this period. Conclusions: E-learning adoption in Iraq during the COVID-19 pandemic was reactive rather than strategically planned. While considerable potential was demonstrated, critical gaps in infrastructure, faculty training, and academic integrity mechanisms must be systematically addressed for sustainable implementation. Limitations: The sample was geographically skewed toward Basrah governorate, limiting the generalizability of findings to allIraqi regions. Contributions: This study provides evidence-based insights into emergency e-learning adoption in a conflict-affected, resource constrained developing country context, offering a foundation for future policy reform in Iraqi higher education